KETERKAITAN POLA PERJALANAN DAN INFORMASI TRANSPORTASI DI KOTA PALEMBANG - Dini Dwi Yurianti; Melawaty Agustien; Rhaptyalyani Herno Della (Jurnal Indonesia Sosial Teknologi, 2025)
This study aims to analyze the relationship between socioeconomic characteristics and travel patterns with the need for a transportation information system in Palembang City. The research is grounded in the growing importance of providing transportation information systems that are responsive to the social and economic dynamics of urban communities. Data were collected through questionnaires distributed to 656 respondents across 18 districts, using a random sampling technique. The sample size was determined using the and Slovin’s formula with a 5% margin of error. The analysis employed descriptive statistics and chi-square tests, based on constructs such as Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Use (ATU), Behavioral Intention to Use (BIU), and Actual Use (AU). The results indicate a significant relationship between both socioeconomic and travel characteristics with the need for a transportation information system. These findings highlight the importance of developing transportation information systems that consider the varying socioeconomic backgrounds and travel behaviors of users. Such systems can play a crucial role in supporting more effective and inclusive transportation planning in Palembang City.